Pengaruh Komite Audit, Komisaris Independen, Kepemilikan Institusional, Free Cash Flow, Dan Leverage - Deannes Isynuwardhana; Magdalena Gina Rahmawati (UNIVED Press, 2023)
Earnings quality reflects the actual performance of the company in generating operating income. Earnings quality can be an indication of the ability of earnings information to respond to the market. In addition, the quality of earnings gets attention and plays an important role in making investment decisions for investors and various parties. This study aims to determine the effect of audit committee, independent commissioners, institutional ownership, free cash flow, and leverage on earnings quality in food and beverage companies. The population in this study were all companies. There are 28 food and beverage companies. While the sample used as many as 20 samples with a total data in this study of 80 data. Then the data in this study were analyzed using descriptive statistics and panel data regression. The results showed that the audit committee, independent commissioners and institutional ownership, free cash flow, and leverage had a significant effect on earnings quality. Partially, audit committee has a significant positive effect, independent commissioners, institutional ownership, and free cash flow has no significant effect, and leverage has a negative significant effect on earnings quality.